If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 6 + 0.25(8 + -12x) 23 = 6 + (8 * 0.25 + -12x * 0.25) 23 = 6 + (2 + -3x) Combine like terms: 6 + 2 = 8 23 = 8 + -3x Solving 23 = 8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 23 + 3x = 8 + -3x + 3x Combine like terms: -3x + 3x = 0 23 + 3x = 8 + 0 23 + 3x = 8 Add '-23' to each side of the equation. 23 + -23 + 3x = 8 + -23 Combine like terms: 23 + -23 = 0 0 + 3x = 8 + -23 3x = 8 + -23 Combine like terms: 8 + -23 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 12=-3b+3 | | 8-4x=72 | | 3(x-4)+2x-7(x-5)=-1 | | 6+.5(x-2)=9 | | 1(x+4)+x-4(x-4)=x+8 | | -5x-3=-48 | | 3n-9=51 | | t+18.=23.9 | | 3x+6=-42 | | 2y+7y=15 | | 4x-4=(x+2) | | x-18=87 | | 5x+6-x^2+4=4x+2 | | 2z-19=5z+2 | | 6m+15=8m-3 | | 5x+6-x^2+10=4x+2 | | 4m+22=7m-2 | | |2/3x+2/3|=2/3 | | 4x^2-21x+35=3x+8 | | 8(t-3)+4+=6(2t+1)-10 | | 0.6x-1.5=1 | | 6x^2-15x=9 | | -2x-6(-x-6)=-4 | | -8-b=6 | | 5x-3(-6x+14)=119 | | 3xy-4-6x+2y=0 | | 3x+5x=9x-8 | | 4x+4(-4x-17)=-164 | | 2a+9b= | | 6x+7(2x-6)=-182 | | 6y=8-0+8y | | y=-7.36x-14354.33 |